2015
DOI: 10.1159/000437299
|View full text |Cite
|
Sign up to set email alerts
|

Depression and Quality of Life in Older Persons: A Review

Abstract: Background: Depression is a prevalent and disabling condition in older persons (≥60 years) that increases the risk of mortality and negatively influences quality of life (QOL). The relationship between depression, or depressive symptoms, and QOL has been increasingly addressed by research in recent years, but a review that can contribute to a better understanding of this relationship in older persons is lacking. Against this background, we undertook a literature review to assess the relationship between depres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

30
301
3
18

Year Published

2017
2017
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 9,491 publications
(352 citation statements)
references
References 119 publications
30
301
3
18
Order By: Relevance
“…the BDI and PHQ-9 scores. Similar relationships between quality of life and depression has been previously reported for different diseases [32][33][34]. Depression and quality of life are both related to general well-being of the patient and emphasise the biopsychosocial aspects of the chronic disease.…”
Section: Discussionsupporting
confidence: 77%
“…the BDI and PHQ-9 scores. Similar relationships between quality of life and depression has been previously reported for different diseases [32][33][34]. Depression and quality of life are both related to general well-being of the patient and emphasise the biopsychosocial aspects of the chronic disease.…”
Section: Discussionsupporting
confidence: 77%
“…Depression was documented as an important predictor of impaired QoL across non-DM patient populations, such as patients with brain tumors and older persons [43, 44]. …”
Section: Discussionmentioning
confidence: 99%
“…(41) Mental conditions like depression are strong predictors of quality of life compared to physical disabilities (42). Literature review findings suggest an obvious and consistent connection between depression and quality of life in both community dwelling and institutional older adults (43). The study of Baker et al on older people who presented in family healthcare centers in Turkey, showed significant relations between having lower educational level and depression and worse scores in quality of life and its sub-dimensions (44).…”
Section: Discussionmentioning
confidence: 99%